An Integrative Curriculum Model for Arabic Instruction Integrating Traditional Values and Modern Pedagogies Pesantren Indonesian - Ismail Akzam; Najmi Hayati (Global Perspectives in Education Journal, 2026)
This study aims to develop an integrative curriculum model for pure Arabic language instruction in Indonesian Islamic boarding schools (pesantren). Traditionally, pesantren emphasize turāth-based instruction through methods such as sorogan and bandongan, fostering deep textual comprehension and scholarly dispositions. However, contemporary educational and societal demands necessitate the development of communicative, academic, and professional Arabic competencies. Employing a Design and Development Research (DDR) methodology, this study collected data from salaf, modern, and semi-modern pesantren through interviews, classroom observations, document analysis, and expert focus group discussions. The data were analyzed thematically and comparatively to examine existing curriculum structures, explore tensions and complementarities between traditional and modern pedagogical approaches, and identify points of convergence between turāth values and communicative, task-based language instruction. The resulting curriculum model delineates philosophical foundations, instructional objectives, content organization, learning strategies, assessment mechanisms, and the creation of an intentional Arabic language environment. Expert validation and limited field try-outs indicate that the proposed model is conceptually robust and practically feasible for gradual implementation, offering a contextually grounded framework for Arabic curriculum reform in pesantren settings.